2017
DOI: 10.4314/tjpr.v16i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of Saikosapoin D on bleomycininduced pulmonary fibrosis in mice via regulation of IL- 33/ST2 pathway

Abstract: Purpose: To investigate the therapeutic effects of saikosapoin D (SSD) on bleomycin (BLM)-induced pulmonary fibrosis (PF) in mice and its probable mechanisms. Methods: PF mice were prepared by intraperitoneal (i.p.) injection of BLM (5 mg/kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Pulmonary fibrosis is characterized by chronic and invasive scar formation and deposition of extracellular matrix (ECM), followed by death due to impaired lung function and respiratory failure [10]. Studies have shown that increased epithelial-mesenchymal transition (EMT) and perturbation of the matrix synthesis/degradation balance are the driving factors in PF [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary fibrosis is characterized by chronic and invasive scar formation and deposition of extracellular matrix (ECM), followed by death due to impaired lung function and respiratory failure [10]. Studies have shown that increased epithelial-mesenchymal transition (EMT) and perturbation of the matrix synthesis/degradation balance are the driving factors in PF [11,12].…”
Section: Discussionmentioning
confidence: 99%